The performance evaluation of ordinary moment resisting frames designed by performance-based plastic design and limit state design. (2015) - Dalal, Sejal P.; Vasanwala, Sandeep A.; Desai, Atul K.
The performance in terms of interstorey drift ratios and failure pattern of ordinary moment resisting frames designed by performance-based plastic design (PBPD) method and limit state design method have been compared in this paper. For this, different study frames were designed using the force based limit state design method and displacement-based performance-based plastic design method. The PBPD frames were designed taking ductility ratio two. Results of static pushover and time history analysis prove the superiority of the PBPD method when compared in terms of interstorey drift ratio and failure pattern.